Jinayat dalam Kasus Penganiayaan Santri Gontor hingga Meninggal Dunia dalam Lingkup Pendidikan - Aisyah Salsabilla; Hanung Wijayanti; Erlina Nur Khasanah (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The human soul and blood are one of things that highly guarded in Islamic law. The recent rise in murder cases caused by the lack of strict laws and the lack of society knowledge about how its important for us to take care of our lives. So, by attracting case that highlighted by the public, this research will attract readers to find out more. This research will give more contribution because the case being discussed will encourage readers to learn more about jinayat. This is what the author does because regarding the Jinayat that raised by the author, is a type of jinayat in the form of persecution in the educational scope which ends in mortlity. Then, this jinayat is inseparable from its punishment, namely “qishash,” which has also been agreed by scholars in this case. Or by paying “diyat” and “kaffarat” because this kaffarat is the right of Allah SWT. This research uses library research with journals as primary data sources and also books, newsletters, and other supporting journals as secondary data sources. The results of this study are the need for strict laws in jinayat cases, especially in cases of persecution, especially in the educational sphere. Where is the scope of education that should provide security and comfort for students when studying, bullying or seniority cases seem to be a natural thing. If this is allowed, apart from damaging the image of an educational institution, it will also make this something permissible. If it is considered as a natural thing, many rights will be taken away.